Arthroscopic bioinductive collagen scaffold augmentation in high-risk posterosuperior rotator cuff tears: clinical and radiological outcomes - Kimmeyer, Michael; Buijze, Geert Alexander; Soares, Madu Nayan; Rab, Peter; Colombini, Antonio Gioele; Diot, Robin; Macken, Arno; Lafosse, Thibault (Journal of Clinical Medicine, 2025)
Background/Objectives: Bioinductive bovine collagen implants (BCI) have been introduced to enhance tendon biology and promote tissue regeneration in r...